ACIDOSIS AND URINE OUTPUT AS INDICATION FOR STARTING CONTINUOUS RENAL REPLACEMENT THERAPY AMONG ACUTE KIDNEY INJURY PATIENTS IN INTENSIVE CARE UNIT: RETROSPECTIVE STUDY AT AL-AHLI HOSPITAL IN HEBRON - Aramin, Osama (An-Najah National University, 2024)
Background: Acute Kidney Injury has a substantial global impact , with an estimated 13 million people affected annually. Acute kidney injury has been reported in 30–60% of hospitalized patients and is prevalent in critically ill individuals and 5– 20% of critically ill patients in the intensive care unit . Up to 4.9% of severely ill patients may require renal replacement therapy. In the last decade the absolute incidence of acute kidney injury has risen, with episodes occurring in. The study aims to investigate acidosis and urine output as indicators for starting continuous renal replacement therapy among acute kidney injury patients in the intensive care unit at AL-Ahli Hospital in the west bank of Palestine . Methods: This Research utilized a Quantitative Retrospective and Descriptive method. The Purposive sampling technique was employed to select participants. The study included all patients diagnosed with acute kidney injury who underwent dialysis all patient with vasopressor , regardless of their age and gender. Demographic data, the presence of comorbidities, the indication for continuous renal replacement therapy, vital signs , urine output, and inotropic , laboratory findings was collected before and after the commencement of continuous renal replacement therapy . Results: The medical records of 96 acute kidney injury patients who received continuous renal replacement therapy between April 2021 -April 2023 was reviewed , was the two -third of patients with comorbidity disease .The mortality rate was 28.1% was 69.8% of patients on mechanical ventilation and all patients was anuria , percentage of males was 56.3% and 43.8% of females , the percentage of survivor patients was 56.5% male and 43.5% of females , went on to receive either chronic hemodialysis or normal kidney function . Conclusion : The most diagnosis for patient on continuous renal replacement therapy commencement septic shock , and the most indication to commencement acidosis and anuria , was the anuria, acidosis, overloaded fluid, & anuria indications was more likely to have survival , comorbidity disease is higher mortality patients on mechanical ventilation less likely to survive , decrease serum creatinine and blood urea nitrogen was not associated with increased mortality .
استخدام ارتفاع معدل الحموضة في الدم وكمية البول كمؤشر لبدء غسيل الكلى المستمر بين مرضى إصابات الكلى الحادة في وحدة العناية المركزة: دراسة بأثر رجعي في المستشفى الأهلي في الخليل